2015
DOI: 10.1515/mms-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

The Static Unbalance Analysis and Its Measurement System For Gimbals Axes of an Inertial Stabilization Platform

Abstract: To reduce the influence of the static unbalance on an infrared missile guidance system, a new static unbalance measure system for the gimbals axes has been developed. Considering the coupling effects caused by a mass eccentricity, the static balance condition and measure sequence for each gimbal axis are obtained. A novel static unbalance test approach is proposed after analyzing the dynamic model of the measured gimbal axis. This approach is to drive the measured gimbal axis to do sinusoidal reciprocating mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…They model the base coordinate system with regard to which the position of a moving object is measured when it rotates around its centre of mass and moves along with it [6][7][8]. In addition, the set motion direction is kept.…”
Section: A Block Diagram Of the Measuring Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They model the base coordinate system with regard to which the position of a moving object is measured when it rotates around its centre of mass and moves along with it [6][7][8]. In addition, the set motion direction is kept.…”
Section: A Block Diagram Of the Measuring Methodsmentioning
confidence: 99%
“…They determine the emergence of a dynamic error along the two measuring coordinates. Within the mathematical models (8) and (9) those effects are divided into the linear and angular ones, whose vectormatrix form can be written as follows:…”
Section: Synthesis Of the Additional Measurement Channelmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu and Zhao [1] presented a novel method to measure UTs in a two axes gimbaled seeker using a measuring instrument with three weight sensors, but this method was insufficient for the higher performances of a seeker owing to the limited sensor's own accuracy. Yang et al [9] developed a method to measure static unbalance of gimbal axis using drive current, and a balanced simulator is used to verify the proposed approach by the load and repeatability tests and the results showed that the developed measuring system is able to achieve a high precision with a greater stability. For FT, direct-driven gimbal is the research object of this paper, so the FT mainly comes from bearings.…”
Section: Introductionmentioning
confidence: 99%
“…Their commercial products have a resolution of 0.1 g cm for a light seeker. Similarly, Yang et al 15 and Zhan et al 16 proposed different prototypes for the static unbalance measurement system. Based on Zhan and colleagues early work, 16,17 the flexure-based mechanism is proposed and acts as a bridge between the double-frame mechanism and a force sensor.…”
Section: Introductionmentioning
confidence: 99%